PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR KETERAMPILAN BERBICARA PESERTA DIDIK KELAS V SD INPRES OEBA 1 - Biredoko, Abelia Larasati; Margareta, Karus M.; Sampe, Markus (Universitas Nusa Cendana, 2024)
This research was conducted in class V SDI Oeba 1 to improve the learning outcomes of students' speaking skills through the application of the Project Based Learning model. This is because there is a problem that the learning outcomes of students' speaking skills are still low so a learning model is needed. This type of research is classroom action research with the research subjects consisting of 22 students. The data collection used observation techniques, test techniques, and documentation. The results showed that after learning by applying the Project Based Learning model, the average achievement of learning completeness of class V students amounted to 45,45% (10 people who were complete) in cycle I and 86,36% (19 people who were complete). It can be concluded that the application of the Project Based Learning model can improve the learning outcomes of speaking skills of fifth-grade students of SDI Oeba 1.